Calix[4]arene-click-cyclodextrin and supramolecular structures with watersoluble NIPAAM-copolymers bearing adamantyl units: “Rings on ring on chain” - Garska, Bernd; Tabatabai, Monir; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2010)
We describe the calixarene-cyclodextrin-coupling via click reaction starting from 5,11,17,23-tetra-tert-butyl-25,27-dipropargylether-26,28-hydroxy-calix[4]arene (calix[4]arene-dipropargylether) (2) onto 6I-azido-6I-deoxycyclomaltoheptaose (3) under microwave assisted conditions. The coupling was proven by MALDI-TOF mass spectrometry, 1H NMR and IR-spectroscopy. The pH dependent supramolecular complex formation with poly(NIPAAM) bearing attached adamantyl units was investigated by dynamic light scattering (DLS) and turbidity measurements.
Keywords: β-cyclodextrin; calix[4]arene; click chemistry; poly(NIPAAM)

(untitled) - Abraham, W. (J. Inclusion Phenom. Macrocyclic Chem., 2002)

(untitled) - Ikeda, A.; Shinkai, S. (J. Am. Chem. Soc., 1994)

(untitled) - Gutsche, C. D.; Alam, I. (Tetrahedron, 1988)

(untitled) - Munteanu, M.; Choi, S. W.; Ritter, H. (Macromolecules, 2009)

(untitled) - De Zorzi, R.; Guidolin, N.; Randaccio, L.; Purrello, R.; Geremia, S. (J. Am. Chem. Soc., 2009)

(untitled) - Kolb, H. C.; Finn, M. G.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2001)

(untitled) - Rostovtsev, V. V.; Green, L. G.; Fokin, V. V.; Sharpless, K. B. (Angew. Chem., 2002)

(untitled) - Zhan, J.; Tian, D.; Li, H.; New, J. (New J. Chem., 2009)

(untitled) - Bew, S. P.; Brimage, R. A.; L'Hermite, N.; Sharma, S. V. (Org. Lett., 2007)

(untitled) - Pérez-Balderas, F.; Ortega-Muñoz, M.; Morales-Sanfrutos, J.; Hernández-Mateo, F.; Calvo-Flores, F. G.; Calvo-Asín, J. A.; Isac-García, J.; Santoyo-González, F. (Org. Lett., 2003)

(untitled) - Ortega-Muñoz, M.; Morales-Sanfrutos, J.; Pérez-Balderas, F.; Hernández-Mateo, F.; Girón-González, M. D.; Sevillano-Tripero, N.; Salto-González, R.; Santoyo-González, F. (Org. Biomol. Chem., 2007)

(untitled) - Chan, T. R.; Hilgraf, R.; Sharpless, K. B.; Fokin, V. V. (Org. Lett., 2004)

(untitled) - Hoogenboom, R.; Moore, B. C.; Schubert, U. S. (Chem. Commun., 2006)

(untitled) - Munteanu, M.; Choi, S. W.; Ritter, H. (Macromolecules, 2008)

(untitled) - Rekharsky, M. V.; Inoue, Y. (Chem. Rev., 1998)

(untitled) - Amajjahe, S.; Ritter, H. (Macromolecules, 2008)

(untitled) - Bonini, M.; Rossi, S.; Karlsson, G.; Almgren, M.; Lo Nostro, P.; Baglioni, P. (Langmuir, 2006)

(untitled) - Saeed, A.; Georget, D. M. R.; Mayes, A. G. (React. Funct. Polym., 2010)

(untitled) - Gutsche, C. D.; Iqbal, M. (Org. Synth., 1990)

(untitled) - Ohga, K.; Takashima, Y.; Takahashi, H.; Kawaguchi, Y.; Yamaguchi, H.; Harada, A. (Macromolecules, 2005)